Idiopathic Autoimmune Thrombocytopenic Purpura (ITP) in adult; review of 50 cases admitted to Baghdad teaching hospital. - Al-Aqabi, Adil S.; Alwan, Alaa F. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Idiopathic autoimmune thrombocytopenia purpura (ITP) is an isolated thrombocytopenia in a patient with no clinically apparent associated conditions or factors that can cause thrombocytopenia. The syndrome of ITP is caused by platelet-specific auto-antibodies that bind to autologous platelets. The diagnosis of ITP is usually a diagnosis of exclusion based on a demonstration of peripheral thrombocytopenia. Steroids are the conventional first-line therapy for adult ITP. Most patients demonstrate a response to steroids within 2 to 4 weeks, but a late response is possible. Patients and Methods: A prospective study on 50 patients with diagnosis consistent with ITP, initially treated by steroid, patients who were non responders to steroids or relapsed following its withdrawal offered splenectomy Results: Ten patients (20 %) had permanent satisfactory remission following steroid therapy, while other 40 patients (80 %) were either non responders (20 patients, 40 %) or relapsed (20 patients, 40%). Twenty patients (40%) underwent splenectomy, all of them initially responded, after 3-6 months, 17 patients of them (85%) were still in complete remission, while 3 patients (15%) were refractory ITP and required further treatment. Conclusion: Steroid therapy is less effective in achieving satisfactory remission in adult patient with ITP; on the other hand, splenectomy had more sustained response after steroid failure.